Transacting With Characters: Teaching Children Perspective Taking With Authentic Literature. Issue 3 (3rd July 2018) - Hodges, Tracey S.; McTigue, Erin; Wright, Katherine Landau; Franks, Amanda D.; Matthews, Sharon D.
ABSTRACT: The present study builds upon established best practices in narrative comprehension instruction by redesigning a story map, to retain the benefits of text structure instruction, while also facilitating students to reach deeper levels of character-based comprehension. Framed in reader response theory, dual coding theory, and developmental theories of perspective taking, children increase their knowledge of text while becoming more capable of taking the perspective of unique characters through intentional transactions. Using an exploratory, single-subject design, the authors centered the reading intervention on comprehending children's literature from two, conflicting character perspectives. The authors documented four 3rd-grade participants' comprehension of plot-based and perspective-taking questions. Additionally, the authors transcribed and analyzed intervention sessions to interpret trends in the students' responses. Our findings indicate modest, but consistent, improvement in reading comprehension.